Sensorimotor Modulation of Mood and Depression: In Search of an Optimal Mode of Stimulation - CANBEYLI, RESIT (Frontiers in Human Neuroscience, 2013)
Depression involves a dysfunction in an affective fronto-limbic circuitry including the prefrontal cortices, several limbic structures including the cingulate cortex, the amygdala and the hippocampus as well as the basal ganglia. A major emphasis of research on the etiology and treatment of mood disorders has been to assess the impact of centrally generated (top-down) processes impacting the affective fronto-limbic circuitry. The present review shows that peripheral (bottom-up) unipolar stimulation via the visual and the auditory modalities as well as by physical exercise modulates mood and depressive symptoms in humans and animals and activates the same central affective neurocircuitry involved in depression. It is proposed that the amygdala serves as a gateway by articulating the mood regulatory sensorimotor stimulation with the central affective circuitry by emotionally labeling and mediating the storage of such emotional events in long-term memory. Since both amelioration and aggravation of mood is shown to be possible by unipolar stimulation, the review suggests that a psychophysical assessment of mood modulation by multi-modal stimulation may uncover mood ameliorative synergisms and serve as adjunctive treatment for depression. Thus, the integrative review not only emphasizes the relevance of investigating the optimal levels of mood regulatory sensorimotor stimulation, but also provides a conceptual springboard for related future research.